DIGITAL MEDIA: PENGGUNAANNYA DALAM PROSES KONSTRUKSI BRANDING WISATA HALAL “THE LIGHT OF ACEH” - Husniati, Ade Muana; Lubis, Suwardi; Yusnadi, Yusnadi (Master of Communication Science Program, Universitas Diponegoro, 2024)
This research aims to analyze the branding process in constructing the halal tourism destination of Aceh Province as